Implementation of Retention Ponds in Flood Management in Sorong Regency – Southwest Papua - Azalia Fajri Yasin; Wahyono Hadi (Litbang Pemas - Universitas Islam Lamongan, 2023)
Mariat Subdistrict is one of the villages affected by the floods in Klasuluk Village, with an area of 0.7995 km2, and Klamalu Village, with an area of 1.0479 km2. This research uses experimental, descriptive, qualitative, and quantitative analysis methods. The results of the analysis and simulation, after being run at intervals of 10 years in the future, there are three flood points in the Klamalu village canal, where the most significant total flood volume is at JN64 146,687 m3/s, the smallest is at JN15 21,232 m3/s, and there are 56 flood points in the Klasuluk village canal, where the largest total flood volume was at JN91 1,863 m3/s and the smallest at JN9 and JN37 0.008 m3/s. The volume of wastewater discharge that enters the drainage is only 1%, so it has no effect. From the data on the dimensions of the retention pond, it is obtained that the wet cross-sectional area is about 145.05 m2, the wet perimeter of the retention pond is 101.69 meters, the hydraulic radius is 1.43 m, the flow velocity is 3.168 m/s, the guard height is 1.22 meters, the water discharge that comes out is 459.51 m3/second.